Smart keychain / Mohd Hifadzly Husrin ... [et al.] - Husrin, Mohd Hifadzly; Douni, Adeylson Ray; Moh Sali, Muhammad Azlan; Rosley, Edrin (2021)
A Smart Keychain is a product that combines a number of cutting-edge technologies with artificial intelligence (AI). AI technology is very common nowadays in the production of modern technology to help users. This Smart Keychain includes AI technology. In addition, this Smart Keychain has a variety of other features to improve the capabilities of its facilities that includes Internet Wi-Fi, GPS tracker, data storage (pen drive),solar energy and USB chargers. The "Smart Keychain" is a very useful tool for travelers since it makes it easier for them to complete their tasks. The objective of this Smart Keychain is to allow users to only use Smart Keychain for certain functions, such as obtaining information about the users' locations by using GPS. The next objective is to provide internet network to users here it is easy to be taken anywhere and can be used to store travel records as well as files in data storage. The Smart Keychain was developed and built to be one of the things that users would benefit in accessing the internet and GPS. This smart Keychain has a number of functions that other ordinary keychains do not have where they could only be used as jewelry. Users of this Smart Keychain can use the Wi-Fi connectivity provided on the Smart Keychain without having to carry a Wi-Fi gadget with them. Users would be able to surf the internet more easily as a result of this. It is also fitted with a GPS device that can assist users with issues such as difficulties in finding locations. It also has a solar energy feature, which eliminates the need to charge the Smart keychain, despite the fact that it has a USB port for charging. Users can use solar energy power to charge the smart Keychain if their region does not have access to electricity. This Smart Keychain is also created specifically to save space and is durable, which means it can fit in a pocket where the exterior component is made of metal, which means it will not break if accidentally dropped. It is also ideal for users to use in all locations or areas without troubling them. Furthermore, this smart Keychain has a solar energy charge feature which allows users to charge the Smart Keychain even when there is no electricity. The result of using this device is that users would be able to access GPS from anywhere because it is fitted with a GPS feature that can assist users in finding locations. Next, since it has a Wi-Fi feature, this Smart key chain can provide Wi-Fi connectivity to its users, making it easier for them to access Wi-Fi and access the internet anywhere. Besides that, users can feel more at ease by using the Smart Keychain because it is powered by solar energy, which eliminates the needs for users to wear the Smart Keychain and makes it easier to use because it can be used at any time and any place. Moreover, since the Smart Keychain is powered by solar energy, users will feel more at ease in using it because they do not need to bring batteries or look for electricity if they run out of power.